2016
DOI: 10.1590/1413-81232015211.05192015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da versão brasileira da escala CRAFFT/CESARE para uso de drogas por adolescentes

Abstract: Avaliação da versão brasileira da escala CRAFFT/CESARE para uso de drogas por adolescentes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The content of the training included: physical and psychological characteristics of adolescence, brain development, national and international epidemiological data on substance use among adolescents, consumption patterns, importance of early identification, risk and protection factors, prevention in the health environment, Portuguese version 3 of the instrument CRAFFT (acronym for Car; Relax; Alone; Forget; Family/Friends; Trouble) for screening and evaluation of seriousness. We also presented the Adolescent SBIRT algorithm 2 (Screening, Brief Intervention and Referral for Treatment), as well as the guidelines for referrals within the city’s network, when necessary.…”
Section: Resultsmentioning
confidence: 99%
“…The content of the training included: physical and psychological characteristics of adolescence, brain development, national and international epidemiological data on substance use among adolescents, consumption patterns, importance of early identification, risk and protection factors, prevention in the health environment, Portuguese version 3 of the instrument CRAFFT (acronym for Car; Relax; Alone; Forget; Family/Friends; Trouble) for screening and evaluation of seriousness. We also presented the Adolescent SBIRT algorithm 2 (Screening, Brief Intervention and Referral for Treatment), as well as the guidelines for referrals within the city’s network, when necessary.…”
Section: Resultsmentioning
confidence: 99%
“…13 For example, adaptations of the CRAFFT for Spanish 20 and for the Brazilian context were evidenced. 35 Still regarding this instrument, it was observed that the reliability (α) ranged from 0.59 to 0.69. This signals low internal consistency.…”
Section: Discussionmentioning
confidence: 97%
“…The extreme values were identified in "use in the last year", in which the item on the use of benzodiazepines presented α=0. 35, and LSD had α=1.0. 24 The ASTEQ-COUNSELOR and the DCI-A-SF presented better alpha values for the items individually and together.…”
Section: Discussionmentioning
confidence: 99%
“…For the care of children at the outpatient clinic, an anamnesis model was built. This anamnesis also includes a habitual physical activity questionnaire [59], Brazilian food safety scale [60], SISVAN food consumption markers questionnaire [61], food frequency questionnaire [62, 63], bullying questionnaire (Kidscape) [64], measurement questionnaire adherence to treatment [65], CRAFFT/CESARE instrument (Car; Relax; Alone; Forget; Family/Friends; Trouble acronym) [66].…”
Section: Methods: Participants Interventions Outcomesmentioning
confidence: 99%